2021
DOI: 10.1101/2021.09.12.21263456
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Predictors of real-world parents’ acceptance to vaccinate their children against the COVID-19

Abstract: Background: As the COVID-19 pandemic continues to threaten public health, the vaccination of children against the disease appears to be a key factor to control the pandemic. Objective: To investigate the prevalence of parents who have vaccinated their children against the COVID-19 and the factors influencing this decision. Methods: We conducted a web-based cross-sectional study in Greece during the first week of September 2021. The study questionnaire was distributed through social media and a convenience samp… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 39 publications
1
4
0
Order By: Relevance
“…This finding is consistent with the literature, which suggests that increased levels of anger are associated with an increased number of negative life events [6]. We note here that in addition to the negative events experienced during the pandemic, Greek nurses were under particular pressure from the state, with laws making COVID-19 vaccination mandatory for healthcare workers [52]. In Greece, health workers have protested against mandatory vaccination plans.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…This finding is consistent with the literature, which suggests that increased levels of anger are associated with an increased number of negative life events [6]. We note here that in addition to the negative events experienced during the pandemic, Greek nurses were under particular pressure from the state, with laws making COVID-19 vaccination mandatory for healthcare workers [52]. In Greece, health workers have protested against mandatory vaccination plans.…”
Section: Discussionsupporting
confidence: 90%
“…In Greece, health workers have protested against mandatory vaccination plans. Mandatory vaccination may have paid off, as over 90% of nurses were vaccinated [52]; however, it is possible that this may explain both the anger and the low intention to receive the COVID-19 vaccine booster, as expressed in the sample. Usually, pressure to vaccinate can lower vaccination intention.…”
Section: Discussionmentioning
confidence: 97%
“…This could be attributed to the reason that individuals anticipate less regret for easily admissible decisions than for less admissible ones. In contrast, the recent studies of Caso et al (2021) and Galanis et al (2021) reported a higher level of anticipated regret for vaccination among a specific groups who abide to the so-called “no-vax” groups. Several studies (e.g., Christy et al, 2016 ; Ng et al, 2020 ; Penţa et al, 2020 ) investigated the potential role of anticipated regret to uptake the HPV and influenza vaccinations respectively.…”
Section: Introductionmentioning
confidence: 76%
“…Behavioral effects of misinformation. The most commonly referenced behavioral effects pertain to health behaviors in response to false claims (e.g., antivaccine movements, speculated vaccine-autism link, genetically modified mosquitos and the Zika virus, COVID-19; Bode & Vraga, 2017;Bronstein et al, 2021;Galanis et al, 2021;Gangarosa et al, 1998;Greene & Murphy, 2021;Joslyn et al, 2021;Kadenko et al, 2021;Loomba et al, 2021;Mug ˘alog ˘lu et al, 2022;van der Linden et al, 2020;Van Prooijen et al, 2021;Xiao & Wong, 2020). The same association has also been made between misinformation associated with anthropogenic climate change and resistance to adopting proenvironmental behaviors (Gimpel et al, 2020;Soutter et al, 2020).…”
Section: Cognitive Effects Of Misinformationmentioning
confidence: 99%